2004
DOI: 10.1007/s00038-004-3149-0
|View full text |Cite
|
Sign up to set email alerts
|

Verbreitung und Sozialprofil der gesundheitsthemenbezogenen Internetnutzung: Ergebnisse einer bundesweiten Telefonumfrage

Abstract: The use of the internet for health care information in Germany is quite different. Questions about consequences remain unanswered. Do the differences increase or do they decrease? And which role does play the health politics? This and other questions could be answered by further studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 7 publications
1
5
0
4
Order By: Relevance
“…The percentage of adolescents looking for health information on the Internet reflected in this study is within the range described in existing literature (40%-73.4%) [4,11-16]. This result is considerably remarkable since most research articles related to this topic have been conducted on adolescents who were native speakers of English and there are no articles on Spanish adolescents.…”
Section: Discussionsupporting
confidence: 76%
“…The percentage of adolescents looking for health information on the Internet reflected in this study is within the range described in existing literature (40%-73.4%) [4,11-16]. This result is considerably remarkable since most research articles related to this topic have been conducted on adolescents who were native speakers of English and there are no articles on Spanish adolescents.…”
Section: Discussionsupporting
confidence: 76%
“…We could not prove whether there were any statistically significant differences in our results regarding age in any of our models. In general, other studies (mostly telephone-based surveys) have shown that online health information seekers are relatively young (eg, [49-53,57,60,61]). However, there has not been sufficient amount of research conducted with a focus on obtaining an online sample.…”
Section: Discussionmentioning
confidence: 99%
“…Andreassen et al [49] also showed an opposite impact of health status on health-related Internet use (ie, those who reported poorer health used the Internet less for health purposes). Neither Hüfken and colleagues [61] nor Dumitru and colleagues [62] could prove higher health-related Internet use for those with poorer health status. However, medical indicators of health, such as a current diagnosis of long-term illness or disability, indicate a higher level of health-related use of the Internet [49].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the number of Internet users has dramatically increased worldwide [1-3,5,9,11-13,15,19,27,36,37], and ISTAT data reveal that this phenomenon has occurred in Italy too [4]. As the mean of European rate of Internet use is about 58%, Italy can be considered as representative of Europe [4,5].…”
Section: Discussionmentioning
confidence: 99%
“…Most published studies, are conducted mainly in Northern European countries [2,7,11,12,21,27], but up to now no studies have been conducted in Italy and there is lack of studies representative of the general population focusing on behavior modifications related to the growing use of the web for health purposes [10,20]. …”
Section: Introductionmentioning
confidence: 99%